2012
DOI: 10.3109/08958378.2012.684450
|View full text |Cite
|
Sign up to set email alerts
|

Repeated inhalation of crack-cocaine affects spermatogenesis in young and adult mice

Abstract: To investigate the effects of repeated crack-cocaine inhalation on spermatogenesis of pubertal and mature Balb/c mice, ten young (Y(ex)) and ten adult (A(ex)) Balb/c mice were exposed to the smoke from 5 g of crack with 57.7% of pure cocaine in an inhalation chamber, 5 days/week for 2 months. The young (Y(c)) and adult (A(c)) control animals (n = 10) were kept in a specially built and controlled animal house facility. The morphologic analysis of both testes of all animals included the analysis of quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
1
6
0
1
Order By: Relevance
“…The negative pressure allowed the use of less drug than required by other devices, and exposure to the smoke of 250 mg of crack cocaine achieved similar plasma cocaine concentrations as reported by Herculiani et al (2009) andPires et al (2012).…”
Section: Discussionsupporting
confidence: 83%
“…The negative pressure allowed the use of less drug than required by other devices, and exposure to the smoke of 250 mg of crack cocaine achieved similar plasma cocaine concentrations as reported by Herculiani et al (2009) andPires et al (2012).…”
Section: Discussionsupporting
confidence: 83%
“…Importantly, the caffeine-cocaine combination induced lower DAZL-positive cell counts than cocaine-alone, indicating that caffeine was able to potentiate cocaine-induced germ cell loss. Accordingly Pires et al [ 48 ] reported that crack cocaine induced a reduction in the number of germ cells and Sertoli cells, leading to a reduction of the tubular diameter in mouse testis. However, we did not detect changes in FSHR protein expression, which is considered a marker of Sertoli cell number [ 44 ], probably indicating that Sertoli cell number may not be altered under our experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, lipid peroxidation is considered to be the main mechanism by which ROS can induce tissue damage leading to impaired cellular function in the testis [ 52 , 53 ]. It has been reported that prolonged exposure to cocaine leads to increased ROS production, germ cell apoptosis, and fibrosis of the seminiferous tubules in the male rat [ 54 , 6 , 51 , 48 ]. Accordingly, we observed that cocaine treatments induced TBARS production indicative of increased lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhaled crack cocaine decreases testicular volume, numbers of Sertoli cells, and impairs spermatid differentiation in mice (Pires et al ., ). Chronic cocaine administration decreases seminiferous tubule diameter and spermatid count in rats (George et al ., ), and has been shown to decrease cAMP responsive element modulator (CREM) expression, which is essential for spermatogenesis (Li et al ., ).…”
Section: Alcohol Tobacco and Drugsmentioning
confidence: 97%